Rotavirus Diarrhea among Children under the Age of Five Years (Medical Forum Monthly, 2024)
Objective: To determine the frequency of Rotavirus (RV) diarrhea among hospitalized children under the age of 5 years.Study Design: A cross sectional / descriptive study.Place and Duration of Study: This study was conducted at the Pediatrics departments of Services Hospital and Arif Memorial Teaching Hospital / Rashid Latif Medical College, Lahore from January 2019 to June 2019.Materials and Methods: A total of 370 children (185 from each center), aged 1 month to 5 years of both genders, hospitalized with symptoms of AGE were enrolled for this study. All the patients were evaluated for the presence of diarrhea, vomiting along with severity of dehydration. Qualitative data like gender, age groups, symptoms, number of vomiting and presence of RV were represented as frequencies and percentages while age was represented as mean and standard deviation. Chi square test was applied to note any possible association of RV with study variables.Results: Out of a total of 370 children, majority, 209 (56.5%) were male and 148 (40.0%) had age between the age of 1 to 12 months, followed by 91 (24.6%) from 13 to 24 months. Mean duration of diarrhea was noted to be 3.47+1.83 days whereas mean number of stools per day was 8.65+2.73. Fever was noted among 217 (58.6%) children. RV positive was noted in 214 (57.8%) children whereas remaining 156 (42.2%) were noted negative. Increasing age and presence of fever were found to have significant association with RV positive children (p value < 0.05).Conclusion: Prevalence of RV was noted to be 58.7% among children aged less than 5 years. Increasing age and presence of fever were found to have significant association with RV positive children